Деякі особливості правового регулювання майнових прав інтелектуальної власності - Микитин, Віталій; Mykytyn, V. (ТНЕУ, 2016)
Розкрито поняття майнових прав інтелектуальної власності. Подано класифікацію майнових прав інтелектуальної власності. Досліджено особливості виключних та невиключних майнових прав інтелектуальної власності. The concept of intellectual property rights is revealed. The classification of intellectual property rights is provided. The peculiarities of exclusive and non-exclusive property rights of intellectual property are researched.
Some special features of the legal regulation of intellectual property rights
Keywords: інтелектуальна власність; майнові права інтелектуальної власності; виключні майнові права інтелектуальної власності; невиключні майнові права інтелектуальної власності; intellectual property; intellectual property rights; exclusive intellectual property rights; non-exclu- sive intellectual property rights